Shape Persistence of Polyproline II Helical Oligoprolines. Issue 30 (18th June 2015) - Garbuio, Luca; Lewandowski, Bartosz; Wilhelm, Patrick; Ziegler, Ludmila; Yulikov, Maxim; Wennemers, Helma; Jeschke, Gunnar
Abstract Oligoprolines are commonly used as molecular scaffolds. Past studies on the persistence length of their secondary structure, the polyproline II (PPII) helix, and on the fraction of backbone cis amide bonds have provided conflicting results. We resolved this debate by studying a series of spin‐labeled proline octadecamers with EPR spectroscopy. Distance distributions between an N‐terminal GdIII‐DOTA (DOTA=1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid) label and a nitroxide label at one of five evenly spaced backbone sites allowed us to discriminate between the flexibility of the PPII helix and the cis amide contributions. An upper limit of 2 % cis amide bonds per residue was found in a 7:3 (v/v) water/glycerol mixture, whereas cis amides were not observed in trifluoroethanol. Extrapolation of Monte Carlo models from the glass transition to ambient temperature predicts a persistence length of ≈3–3.5 nm in both solvents. The method is generally applicable to any type of oligomer for which the persistence length is of interest.